RESOLUSI SPASIAL, TEMPORAL DAN SPEKTRAL PADA CITRA SATELIT LANDSAT, SPOT DAN IKONOS - Suwargana, Nana (Jurnal Ilmiah Widya, 2013)
Satellite remote sensing data is one of the data to obtain natural phenomena on Earth's surface obtained by a media device (sensor) mounted on an aircraft or a satellite. The purpose of this study is to elaborate on the technical characteristics of the remote sensing satellite imagery produced by a variety of earth, satellite Landsat, Spot and Ikonos data and the potential applications for various fields. The method used literature study, internet media and the data was analyzed descriptively. The results showed that: (1) The sensor can detect an object through measurements of the Earth's surface reflectance or emission of electromagnetic waves by the medium. (2) Various types of remote sensing satellite data received by the sensor have different characteristics, so the potential utilization also vary. (3) Characteristics generated by satellite images of the earth which are spatial resolution, temporal resolution and spectral resolution.